Bizarre tail weaponry in a transitional ankylosaur from subantarctic Chile - Soto Acuña, Sergio; Vargas, Alexander O.; Kaluza, Jonatan Ezequiel; Leppe, Marcelo A.; Botelho, Joao F.; Palma Liberona, José; Gutstein, Carolina Simon; Fernández, Roy A.; Ortiz, Héctor; Milla, Verónica; Aravena, Bárbara; Manríquez, Leslie M. E.; et al. (Nature)
Armoured dinosaurs are well known for their evolution of specialized tail weapons— paired tail spikes in stegosaurs and heavy tail clubs in advanced ankylosaurs1 . Armoured dinosaurs from southern Gondwana are rare and enigmatic, but probably include the earliest branches of Ankylosauria2–4 . Here we describe a mostly complete, semi-articulated skeleton of a small (approximately 2 m) armoured dinosaur from the late Cretaceous period of Magallanes in southernmost Chile, a region that is biogeographically related to West Antarctica5 . Stegouros elengassen gen. et sp. nov. evolved a large tail weapon unlike any dinosaur: a fat, frond-like structure formed by seven pairs of laterally projecting osteoderms encasing the distal half of the tail. Stegouros shows ankylosaurian cranial characters, but a largely ancestral postcranial skeleton, with some stegosaur-like characters. Phylogenetic analyses placed Stegouros in Ankylosauria; specifcally, it is related to Kunbarrasaurus from Australia6 and Antarctopelta from Antarctica7 , forming a clade of Gondwanan ankylosaurs that split earliest from all other ankylosaurs. The large osteoderms and specialized tail vertebrae in Antarctopelta suggest that it had a tail weapon similar to Stegouros. We propose a new clade, the Parankylosauria, to include the frst ancestor of Stegouros— but not Ankylosaurus—and all descendants of that ancestor. Fil: Soto Acuña, Sergio. Universidad de Chile; Chile Fil: Vargas, Alexander O. Universidad de Chile; Chile Fil: Kaluza, Jonatan Ezequiel. Universidad de Chile; Chile. Universidad Maimónides; Argentina. Fundación de Historia Natural Félix de Azara; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Leppe, Marcelo A. Universidad de Chile; Chile. Instituto Nacional Antártico Chileno; Chile Fil: Botelho, Joao F. Universidad de Chile; Chile. Pontificia Universidad Católica de Chile; Chile Fil: Palma Liberona, José. Universidad de Chile; Chile. Pontificia Universidad Católica de Chile; Chile Fil: ...